Kurikulum Matematika Australia: Tinjauan Sistematis tentang Konteks, Konten dan Proses - Ahmad Gufron; Iwan Junaedi; Mulyono Mulyono (Syntax Corporation Indonesia, 2025)
This research aims to provide a systematic review of the Australian Mathematics Curriculum with a focus on its context, content and implementation process, and evaluate its relevance in global mathematics education. Through a literature review approach, this study collected and analyzed relevant literature on curriculum development, teaching strategies and challenges in the implementation of the Australian Mathematics Curriculum, comparing it with curricula in other countries. The research method used is a literature review, by examining academic sources including journal articles, books, research reports from the last 10 years, and official documents related to the mathematics curriculum in Australia and other countries. The data collected was then thematically analyzed to identify strengths and weaknesses in the curriculum approach, and to relate the findings to the global context. The results showed that. 1) context description; The Australian Mathematics Curriculum is driven by an inclusive and competency-based national education policy, with an emphasis on developing critical thinking skills, problem solving, and the use of technology in learning. 2) Description of curriculum content includes three main strands: Number and Algebra, Measurement and Geometry, and Statistics and Probability, which are designed to provide a comprehensive understanding of mathematics, with a progressive and graduated approach from primary to secondary levels. 3) Process Description; the implementation of the curriculum involved inquiry-based teaching, problem solving, and technology integration, despite facing challenges related to teacher training, infrastructure, and access gaps in rural and remote areas.